Expression of nuclear Methyl-CpG binding protein 2 (Mecp2) is dependent on neuronal stimulation and application of Insulin-like growth factor 1. (16th May 2016) - Tropea, Daniela; Mortimer, Niall; Bellini, Stefania; Molinos, Ines; Sanfeliu, Albert; Shovlin, Stephen; McAllister, Donna; Gill, Michael; Mitchell, Kevin; Corvin, Aiden
Highlights: Mecp2 protein nuclear expression is dependent on neuronal stimulation. Increase in the cellular activity induce a decrease in Mecp2 nuclear staining. Insulin-like factor 1 (IGF1) administration induces an increase in Mecp2 expression. Abstract: Methyl-CpG binding protein 2 (MECP2) is a chromosome-binding protein that regulates the development and maintenance of brain circuits. Altered function of the protein product of MECP2 plays an important role in the etiology of many neurodevelopmental disorders. Mutations involving a loss of function are implicated in the etiology of Rett syndrome, intellectual disability, psychosis and severe encephalopathy. Conversely, MECP2 duplications have been identified in autism and intellectual disability. MECP2 action is dependent on neuronal function, as the DNA binding is modulated by activity, and it is phosphorylated in response to stimulation. Although MECP2 is considered a major risk factor for neurodevelopmental disorders, and it is a mediator of activity-dependent mechanisms, the expression levels in response to neuronal activity have never been measured. We studied the expression of Mecp2 protein and RNA in mice neuronal cultures in response to different stimulation conditions and in the presence of insulin-like growth factor1 (IGF1): a growth factor involved in brain development and plasticity. The stimulation protocols were selected according to their ability to induce different forms of synaptic plasticity: rapid depolarization, feed-forward plasticity (LTP, LTD) and feedback forms of plasticity (TTX, KCl). We find a significant reduction of Mecp2 protein nuclear expression in neurons in response to stimuli that induce a potentiation of neuronal response, suggesting that Mecp2 protein expression is modulated by neuronal activation. Application of IGF1 to the cultures induces an increase in the expression of Mecp2 transcript and nuclear Mecp2 protein in neurons. These results show that Mecp2 is responsive to neuronal stimulation and IGF1, and different stimuli have different effects on Mecp2 expression; this differential response may have downstream effects on functional mechanisms regulating brain development and plasticity.